Застосування нового аналітично-числового методу Остроградського до розв'язування плоскої задачі теорії пружності - Ревенко, В.П. (Видавничий дім "Академперіодика" НАН України, 2007)
A boundary-value problem for the biharmonic equation is solved, and the stress-strain state (SSS) of a rectangular plate loaded on the sides by forces is defined. The SSS is presented in the form of a series in specially constructed Saint-Venant functions. The series coefficients are found from the condition of minimum of the deviation square integral of a solution from the given boundary conditions on the plate sides. The Bessel inequality is proved, and the effective valuation of the exactness of the general solution is given. The results of numerical analysis of the stresses are presented.